SEMANTIC FEATURES OF TONGUE TWISTERS FORMED ON THE SNOW LEXICON IN UZBEK AND ENGLISH LANGUAGES (Web of Teachers: Inderscience Research, 2025)
This article investigates the semantic properties of tongue twisters constructed using the snow lexicon in Uzbek and English languages. Through a comparative linguistic analysis, it explores lexical-semantic fields, phonetic symbolism, cultural connotations, and structural patterns formed by snow-related vocabulary. The study reveals both cross-linguistic similarities—such as reliance on alliteration, onomatopoeia, and sound symbolism—and language-specific features rooted in climate, worldview, and folklore traditions. The findings demonstrate how snow lexemes enrich tongue twisters in terms of imagery, acoustic effect, and cognitive associations.